Treating exertional heat stroke: Limited understanding of the female response to cold water immersion - Hutchins, Kate P.; Minett, Geoffrey M.; Stewart, Ian B. (Frontiers in Physiology, 2022)
According to an expansive body of research and best practice statements, whole-body cold water immersion is the gold standard treatment for exertional heat stroke. However, as this founding evidence was predominantly drawn from males, the current guidelines for treatment are being applied to women without validation. Given the recognised differences in thermal responses experienced by men and women, all-encompassing exertional heat stroke treatment advice may not effectively protect both sexes. In fact, recent evidence suggests that hyperthermic women cool faster than hyperthermic men during cold water immersion. This raises the question of whether overcooling is risked if the present guidelines are followed. The current mini-review examined the literature on women’s response to cold water immersion as a treatment for exertional heat stroke and aimed to clarify whether the current guidelines have appropriately considered research investigating women. The potential implications of applying these guidelines to women were also discussed.